Experimental and theoretical study of 3p photoionization and subsequent Auger decay in atomic chromium. (December 2015) - Keskinen, J.; Huttula, S.-M.; Mäkinen, A.; Patanen, M.; Huttula, M.
Abstract: 3 p photoionization and subsequent low kinetic energy Coster–Kronig and super Coster–Kronig Auger decay have been studied in atomic chromium. The binding energies, line widths, and relative intensities for the transitions seen in the synchrotron radiation excited 3 p photoelectron spectrum are determined. The high resolution M 2, 3 M 4, 5 M 4, 5 and M 2, 3 M 4, 5 N 1 Auger electron spectra following the electron impact excited 3 p ionization are presented and the kinetic energies, relative intensities, and identifications are given for the main lines. The experimental findings are compared with the theoretical predictions obtained from Hartree–Fock and multiconfiguration Dirac–Fock approaches. Abstract : Highlights: Synchrotron radiation excited Cr 3 p photoelectron spectrum. High resolution Auger decay following Cr 3 p ionization. Widths of the photoionized states. Identification and energies of the Auger decay.